The Fast Real-time Assessment of Combination Therapies in Immuno-ONcology (FRACTION) program: innovative, high-throughput clinical screening of immunotherapies. (November 2018) - Simonsen, Katy L.; Fracasso, Paula M.; Bernstein, Steven H.; Wind-Rotolo, Megan; Gupta, Manish; Comprelli, Adriana; Reilly, Timothy P.; Cassidy, Jim
Abstract: Background: The unprecedented success of immuno-oncology (I-O) agents targeting the cytotoxic T lymphocyte–associated antigen 4 and programmed death-1/programmed death-ligand 1 pathways has stimulated the rapid development of other I-O agents against novel immune targets. Bristol-Myers Squibb has designed a novel phase II platform trial, the Fast Real-time Assessment of Combination Therapies in Immuno-ONcology (FRACTION) Program, to efficiently identify promising combinations for patients with specific malignancies. The concept and study design of the FRACTION Program—currently ongoing in patients with advanced non-small-cell lung cancer (FRACTION-Lung), gastric cancer (FRACTION-Gastric Cancer) and renal cell carcinoma (FRACTION-RCC)—are described. Methods: The FRACTION Program comprises open-label, phase II studies that use adaptive randomisation designs with rolling combination regimens. Master Protocols provide the overall study design framework, whereas Sub-Protocols introduced over time provide details on specific I-O combination therapies to which patients may be randomised. In a Master Protocol, patients are enrolled into different Study Tracks based on characteristics such as prior I-O therapy experience. Patients who progress may be rerandomised to other combination regimens from any ongoing Sub-Protocol. Primary objectives are to assess objective response rate, median duration of response and progression-free survival rate at 24 weeks; the secondary objective is to investigate safety and tolerability. Biomarker collection before and on treatment will facilitate identification of patient subsets who benefit most from each therapy. Conclusions: The FRACTION Program allows for the evaluation of multiple I-O combinations through individual studies for specific tumours using an adaptive trial design and continuous enrolment. Highlights: The Fast Real-time Assessment of Combination Therapies in Immuno-ONcology (FRACTION) Program is an innovative and adaptive clinical trial program. FRACTION accelerates access to -I-O therapies for patients with advanced tumours. FRACTION aims to enhance selection of transformational -I-O combinations.